2010
DOI: 10.1590/s1519-69842010000500019
|View full text |Cite
|
Sign up to set email alerts
|

Colony size, sex ratio and cohabitation in roosts of Phyllostomus hastatus (Pallas) (Chiroptera: Phyllostomidae)

Abstract: Phyllostomus hastatus bat is species broadly distributed over the Neotropical region, which uses as diurnal roosts caves, hollow trees, palm leaves and human buildings. Thirteen diurnal roosts of P. hastatus were analysed from 1990 to 2009 in several localities of Rio de Janeiro State, regarding environment (rural, urban or protected area), type of roost (hollow tree, basement or roof), sex ratio and cohabitation. A nocturnal roost was also analysed. Sex ratio of P. hastatus varied considerably among roosts wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
(27 reference statements)
0
12
0
3
Order By: Relevance
“…La mayoría de los especímenes presentaban áreas del cuerpo sin pelos, probablemente causadas por alguna enfermedad o parasitismo similar a la sarna de animales domésticos; también llamaba la atención la presencia de manchas de albinismo en la mayoría de los ejemplares. Junto a estos especímenes se colectó un ejemplar de Molossus molossus (Pallas), asociación registrada también en Brasil por Costa et al (2010). Los especímenes de Varillal se refugiaban entre las palmas del techo de paja de una "maloca" (construcción comunitaria con techo de palma).…”
Section: Phyllostomus Hastatus (Pallasunclassified
“…La mayoría de los especímenes presentaban áreas del cuerpo sin pelos, probablemente causadas por alguna enfermedad o parasitismo similar a la sarna de animales domésticos; también llamaba la atención la presencia de manchas de albinismo en la mayoría de los ejemplares. Junto a estos especímenes se colectó un ejemplar de Molossus molossus (Pallas), asociación registrada también en Brasil por Costa et al (2010). Los especímenes de Varillal se refugiaban entre las palmas del techo de paja de una "maloca" (construcción comunitaria con techo de palma).…”
Section: Phyllostomus Hastatus (Pallasunclassified
“…Since roosts may have different sex ratios (MCCRAKEN;BRADBURY, 1981;COSTA et al, 2010), different prevalence and intensity values may be observed, as in the present study. Constant roost changes may also be responsible for re-infestation and dispersal of ectoparasites within the bat population.…”
Section: Discussionmentioning
confidence: 56%
“…Harems are stable, with females living together for consecutive years, whereas long cohesion has not been observed in bachelor groups. However, even males form clusters (COSTA et al, 2010), and therefore aggregation does not explain the higher infestation observed on females. Long permanence in the same roost may result in higher infestation (LEWIS, 1995;KERTH, 2006KERTH, , 2007PATTERSON et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In harem species a sexual proportion skewed to females can be expected (Mello and Fernandez, 2000), but this data, using long term sampling and a great variety of locals probably inhibit this difference as obtained by Costa et al (2010) in other harem bat species. Subadult bats were more netted from November to February, period that is expect the independence of the youngs borned in each year and less frequent from May to August, when few females showed reproductive activity.…”
Section: Discussionmentioning
confidence: 97%